2017
DOI: 10.1016/j.jmbbm.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties and strain-to-crack-initiation of calcium phosphate bone cements: Revelations of a high-resolution measurement technique

Abstract: Calcium phosphate cements (CPCs) should ideally have mechanical properties similar to those of the bone tissue the material is used to replace or repair. Usually, the compressive strength of the CPCs is reported and, more rarely, the elastic modulus. Conversely, scarce or no data are available on Poisson's ratio and strain-to-crack-initiation. This is unfortunate, as data on the elastic response is key to, e.g., numerical model accuracy. In this study, the compressive behaviour of brushite, monetite and apatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 58 publications
1
20
0
2
Order By: Relevance
“…Although they should mimic the mechanical behavior of bone tissue, their mechanical properties are still far from optimal. In fact, CPCs are brittle [ 2 , 3 , 4 ], and the limited data available in the literature suggests that this material can only withstand small strain levels (range 0.1–0.2%) before failure [ 5 , 6 ]. Therefore, new CPC formulations are still under development [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although they should mimic the mechanical behavior of bone tissue, their mechanical properties are still far from optimal. In fact, CPCs are brittle [ 2 , 3 , 4 ], and the limited data available in the literature suggests that this material can only withstand small strain levels (range 0.1–0.2%) before failure [ 5 , 6 ]. Therefore, new CPC formulations are still under development [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the bending strength values reported for CPCs are typically in the range of 5-15 MPa (Martin & Brown 1995;Ginebra et al 2001), close to that of trabecular bone (estimated between 10 and 20 MPa) (Barinov 2010), their strain to failure is much lower . The brittleness of CPCs has recently been highlighted in a report on their strain-to-crack-initiation, which amounted to a mere 0.2% in compression (Ajaxon et al 2017). An improvement of the mechanical performance of these materials, and particularly a mitigation of their brittle behavior, would significantly extend the applicability of CPCs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been mentioned in the literature that mechanical properties of self-setting ceramics are lower than high-temperature sintering ceramics [ 56 ]. Nevertheless, the scaffolds from this study still showed values in the physiological range reported for trabecular bone [ 54 , 55 ]. While sintering may further improve the mechanical strength of the constructs, this would prevent the direct incorporation and anchoring of lowmelting point thermoplastic polymers as presented in this study as a strategy to improve bone-to-soft tissue interfaces.…”
Section: Resultsmentioning
confidence: 82%
“…Tangent modulus, ultimate strength and energy to failure were characterized by performing unconfined compression tests and calculated from the stress-strain curves ( figure 4(B) , supple-mentary figures S4(A) and (B) ). Importantly, all formulations and pore designs exhibited compressive properties in the range of cancellous bone [ 54 , 55 ]. Tangent modulus, ultimate strength and energy to failure of scaffolds made from both NC-PCaP and C-PCaP gradually decreased with increasing porosity, as expected ( figures 4(B), (D) and supplementary figure S4(C) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation